Some Issues Involved in Guaranteed Wage and Employment Demands - White, Rodney (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 1955)
SummaryOne of the most important aspects of this year's negotiations in the automobile and other industries is the demand by the unions for some form of guaranteed employment plan. In this article the author examines the basic features of wage and employment guarantees and how they are viewed by different groups and suggests some of the problems involved in implementing these guarantees.